Estimating the cost of a smoking employee. Issue 5 (3rd June 2013) - Berman, Micah; Crane, Rob; Seiber, Eric; Munur, Mehmet
Abstract : Objective: We attempted to estimate the excess annual costs that a US private employer may attribute to employing an individual who smokes tobacco as compared to a non-smoking employee. Design: Reviewing and synthesising previous literature estimating certain discrete costs associated with smoking employees, we developed a cost estimation approach that approximates the total of such costs for US employers. We examined absenteeism, presenteesim, smoking breaks, healthcare costs and pension benefits for smokers. Results: Our best estimate of the annual excess cost to employ a smoker is 5816. This estimate should be taken as a general indicator of the extent of excess costs, not as a predictive point value. Conclusions: Employees who smoke impose significant excess costs on private employers. The results of this study may help inform employer decisions about tobacco-related policies.